The body image of Asian American men: a phenomenological analysis - Chang, Lynn, author; Rickard, Kathryn M., advisor; Borrayo, Evelinn, advisor; Xing, Jun, committee member; Volbrecht, Vicki, committee member (Colorado State University. Libraries, 2003)
It was once believed that body image concerns were limited to young European American women (Collins, 1988). Today, researchers believe that appearance-related issues affect individuals across gender, age, and racial boundaries (Story, French, Resnick, & Blum, 1995). Past studies have provided mixed conclusions regarding the body image issues of Asian American men (Story et al., 1995; Gross & Rosen, 1988; Mintz & Kashubeck, 1999). It was believed that a qualitative approach would enable researchers to better understand the phenomenon by examining it from the individual's perspective. Ten Asian American male undergraduate student participants completed the acculturation measure SL-ASIA (Suinn, Rickard-Figueroa, Lew, & Vigil, 1987), the ethnic identity measure Orthogonal Cultural Identification Questionnaire (Oetting & Beauvais, 1990-1991), and an individual interview. Four salient themes emerged from the interviews. First, there was limited expressiveness and awareness of their body image experiences. Their responses were often vague or contradictory in nature. Second, the ability to depersonalize negative feelings about one's body was noted as a unique way of expressing one's body satisfaction. Though several participants expressed much negativity regarding their body satisfaction, they seemed to be able to remove themselves from it emotionally. Third, factors that influenced and reinforced their body image were friends, childhood experiences, family, society, media, and the opposite sex. Fourth, the participants felt that their ethnicity had little to do with their body image. Though this aspect was specifically probed, the interviewees denied that their physical Asian characteristics were made the subject of ridicule. Possible explanations of these findings are explored. There were no significant findings regarding the relationship between ethnic identity or acculturation and body image. The small, homogeneous sample size may have related to these inconclusive findings. Given the limitations of qualitative studies, it is hoped that the rich, descriptive results of these in-depth interviews help researchers better understand the body image experiences of Asian American men and lend impetus to future studies.
Keywords: social psychology; minority and ethnic groups; sociology; ethnic studies